Management Driven Structured Reporting in Ovarian Cancer - Anuradha Chandramohan; Sourav Panda; Anitha Thomas; Rachel Chandy; Anjana Joel; Thomas Samuel Ram; Abraham Peedicayil (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Since majority (80%) of ovarian cancer patients present at an advanced stage, imaging performed on these patients have numerous findings. The combination of multiple findings on imaging, complexity of anatomical structures which are involved in ovarian cancer, and the need to perceive certain subtle imaging features which would impact management often makes it challenging to systematically review images of these patients. Similarly, it is difficult to effectively communicate these findings in radiology reports. Structured reporting that is geared toward clinical decision-making has been an area of recognized need. An understanding of the review areas, which aid clinical decision-making in a multidisciplinary team setting at our institution led us to the proposed structured reporting template for ovarian cancer. Through this review, the authors would like to share this reporting template with examples.